Retirement in Italy and Norway - Ugo Colombino; Erik Hernæs; Zhyiang Jia; Steinar Strøm (University of Oslo, Department of Economics, 2003)
A structural model for retirement and employment based on a flexible, parametric utility function is developed. The model requires only cross section data and is estimated on survey data for Italy and register data for Norway. The estimates indicate that the preference structure among middle-aged Italian males and Norwegian males and females who are approaching retirement has strong similarities. The utility function estimates from a model with no consumption smoothing, seem more reasonable than estimates from a model with a perfect credit market. Policy simulations indicate a somewhat stronger response to cuts in pension benefits in Norway than in Italy.
Keywords: D10; H55; J26; 330; Retirement; inter-temporal interpretation; estimates and policy; simulations; Italy; Norway; Altersgrenze; Zeitpräferenz; Schätzung; Italien; Norwegen